Novel insights into the polycythemia–paraganglioma–somatostatinoma syndrome. Issue 12 (December 2016) - Därr, Roland; Nambuba, Joan; Del Rivero, Jaydira; Janssen, Ingo; Merino, Maria; Todorovic, Milena; Balint, Bela; Jochmanova, Ivana; Prchal, Josef T; Lechan, Ronald M; Tischler, Arthur S; Popovic, Vera; et al.
Abstract : Worldwide, the syndromes of paraganglioma (PGL), somatostatinoma (SOM) and early childhood polycythemia are described in only a few patients with somatic mutations in the hypoxia-inducible factor 2 alpha ( HIF2A ). This study provides detailed information about the clinical aspects and course of 7 patients with this syndrome and brings into perspective these experiences with the pertinent literature. Six females and one male presented at a median age of 28 years (range 11–46). Two were found to have HIF2A somatic mosaicism. No relatives were affected. All patients were diagnosed with polycythemia before age 8 and before PGL/SOM developed. PGLs were found at a median age of 17 years (range 8–38) and SOMs at 29 years (range 22–38). PGLs were multiple, recurrent and metastatic in 100, 100 and 29% of all cases, and SOMs in 40, 40 and 60%, respectively. All PGLs were primarily norepinephrine-producing. All patients had abnormal ophthalmologic findings and those with SOMs had gallbladder disease. Computed tomography (CT) and magnetic resonance imaging revealed cystic lesions at multiple sites and hemangiomas in 4 patients (57%), previously thought to be pathognomonic for von Hippel–Lindau disease. The most accurate radiopharmaceutical to detect PGL appeared to be [ 18 F]-fluorodihydroxyphenylalanine ([ 18 F]-FDOPA). Therefore, [ 18 F]-FDOPA PET/CT, not [ 68 Ga]-(DOTA)-[Tyr3]-octreotate ([ 68 Ga]-DOTATATE) PET/CT is recommended for tumor localization and aftercare in this syndrome. The long-term prognosis of the syndrome is unknown. However, to date no deaths occurred after 6 years follow-up. Physicians should be aware of this unique syndrome and its diagnostic and therapeutic challenges.